WANPRESTASI DALAM PERJANJIAN PENGIKATAN JUAL BELI TANAH DAN BANGUNAN RUMAH - Roberta R.P Situmorang; Velda Anastasia S; Anissa Shiva Shafira; Dwi Desi Yayi Tarina (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
The Land and Building Sale and Purchase Agreement is a preliminary agreement prior to the signing of a valid sale and purchase deed, and generally contains provisions that regulate the obligations of the parties. Referring to Article 1457 of the Civil Code (“Civil Code”), sale and purchase is an agreement in which one party binds himself to hand over an item and the other party to pay the promised price. Buying and selling land and house buildings is a complex transaction and is potentially vulnerable to legal conflicts, especially in the context of default. and carrying out its obligations according to what has been agreed to to the second party, such as helping to change the name of the land certificate and house building from the first party to the second party.